Smartening sustainable development in cities: Strengthening the theoretical linkage between smart cities and SDGs. (May 2022) - Blasi, S.; Ganzaroli, A.; De Noni, I.
Highlights: The convergence between smart cities and SDGs literature is still in its infancy The literature on SDGs has developed a peculiar capacity to analyse problems related to social inclusion, equity, and poverty. Sustainability, resource management, governance, innovation, and collaboration are the concepts in common between these two fields of literature. Abstract: In 2015, the United Nations General Assembly set up 17 interlinked global goals designed to be a blueprint to achieve a better and more sustainable future for all, which are commonly addressed as SDGs. In this blueprint, cities are seen as a hotspot for achieving those goals by 2030. In this context, cities, through smart technologies, are engaging in generating a sustainable ecosystem that is inclusive of social and environmental concerns. The main objective of this paper is to assess the effect of SDGs institutionalization on the concept of smart sustainable cities. To this end, we review the literature on smart cities and SDGs to analyze the degree of alignment and potential areas of development. The results reveal the existence of brokerage keywords, which rank high in both fields of the literature, but are missing from the portfolio of overlapping keywords. This is the case for water management, energy, governance, and collaboration. While concepts such as sustainability, waste management, civic engagement, and innovation are in common, albeit explored differently.